Analysis of the relationship between length and weight, gonad maturity level, gonad maturity index and fecundity of the yellowstripe scad (Selaroides leptolepis Cuvier, 1833) - Miranti Khairunisa Abudi; La Nane (Fisheries and Society Publisher, 2021)
Yellowstripe scad (Selaroides leptopleptis) is an economically important fish species from small pelagic fishery resources in TPI, Tenda Village, Hulonthalangi Subdistrict, Gorontalo City. Gonad Maturity (TKG), Gonad Maturity Index (IKG), and condition factors of yellowstripe scad. The results of the research yellowstripe scad (Selaroides leptolepis) between males and females have a gonadal maturity index (IKG) of 0.013%–0.025%, with the number of gonadal maturity levels (TKG) I is 24, TKG II is 22, TKG III is 10 tail, TKG IV is 1 individual and TKG V is 5 individuals. The value of relationship value between length and weight of yellowstripe scad (Selaroides leptolepis) is W=0,3945L1,0487 with a value of b<3 (negative allometric). The relative condition factors varied from 0.9051–1.069. Meanwhile, the fecundity of yellowstripe scad (Selaroides leptolepis) ranged from 23.760-78.000 eggs.